1992
DOI: 10.1021/ma00041a014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization techniques for the study of silica fragmentation in the early stages of ethylene polymerization

Abstract: Cryomicrotomy of embedded particles, sequential removal of polymeric components via carefully controlled plasma ashing, and a combination of these preparative techniques allowed the microscopic characterization of the internal morphology and chemical composition of inorganic supports, supported catalysts, growing and fully grown polymer particles, and extruded films at submicrometer resolution.Videotaped polymerizations under a microscope at commercially used pressures provided additional insights into the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 0 publications
2
51
0
3
Order By: Relevance
“…Fragmentation continued until the catalyst fragments became smallest in size as subunits or subparticles, which remained dispersed and entrapped in the growing polymer mass and acted as a nucleus for further polymer growth. This kind of substantial fragmentation is well documented in the literature, for example in the studies by Buls et al 28 and, later, by Ferrero et al, 29 Niegisch et al, 30 and Kakugo et al 31,32 Another advantage of molten polymer analysis is the ability to study the activity distribution of single catalyst particles. This can be demonstrated simply by comparing the degree of support disintegration in different molten polymer particles.…”
Section: Catalyst Particle Fragmentation Processmentioning
confidence: 81%
“…Fragmentation continued until the catalyst fragments became smallest in size as subunits or subparticles, which remained dispersed and entrapped in the growing polymer mass and acted as a nucleus for further polymer growth. This kind of substantial fragmentation is well documented in the literature, for example in the studies by Buls et al 28 and, later, by Ferrero et al, 29 Niegisch et al, 30 and Kakugo et al 31,32 Another advantage of molten polymer analysis is the ability to study the activity distribution of single catalyst particles. This can be demonstrated simply by comparing the degree of support disintegration in different molten polymer particles.…”
Section: Catalyst Particle Fragmentation Processmentioning
confidence: 81%
“…The final shape of polyolefin particles conforms to the initial shape of catalyst particles for a broad range of experimental conditions. 26,27 However, the fast growth of polymer could prevent the regular replication of the shape and the distribution of particle sizes. [28][29][30] Czaja and Król 31 reported that the non-pre-polymerized MgCl 2 -supported Ti catalyst produced irregularly shaped polypropylene particles, whereas the prepolymerized catalyst particles yielded oval particles with a nearly uniform distribution of shape and size.…”
Section: Experimental Observations Of Particle Morphologymentioning
confidence: 99%
“…Já foram desenvolvidos trabalhos com o objetivo de elucidar o mecanismo de fragmentação para diferentes tipos de suportes e nas mais variadas condições experimentais usando técnicas como: isotermas de adsorção-dessorção de nitrogênio (método BET), microscopia eletrônica de varredura (SEM), microscopia eletrônica de transmissão (TEM) e, também, modelagem matemática. [36][37][38][39][40][41][42][43][44][45] Os resultados mais relevantes, geralmente obtidos de técnicas que envolvem diversos tipos de microscopia, mostram que o polímero nascente é forçado a preencher os espaços disponíveis na estrutura do suporte, gerando uma unidade compacta e comprimida de polímero, que exerce uma força acentuada sobre as paredes dos poros, levando a sua fragmentação. 41,45 Desse contexto surgem duas forças opostas: a pressão exercida pelo polímero sobre as paredes dos poros e, a contra-pressão oriunda da resistência do material do suporte.…”
Section: Materias Empregados Como Suportesunclassified
“…[36][37][38][39][40][41][42][43][44][45] Os resultados mais relevantes, geralmente obtidos de técnicas que envolvem diversos tipos de microscopia, mostram que o polímero nascente é forçado a preencher os espaços disponíveis na estrutura do suporte, gerando uma unidade compacta e comprimida de polímero, que exerce uma força acentuada sobre as paredes dos poros, levando a sua fragmentação. 41,45 Desse contexto surgem duas forças opostas: a pressão exercida pelo polímero sobre as paredes dos poros e, a contra-pressão oriunda da resistência do material do suporte. Considerando que o suporte só fragmenta quando a força de pressão do polímero é superior à resistência da parede do poro, a pressão dentro dos poros é facilmente estimada como da mesma ordem da resistência à compressão do material, que, no caso da sí-lica, é de aproximadamente 10 4 atm.…”
Section: Materias Empregados Como Suportesunclassified
See 1 more Smart Citation